Qualitative Research for a Digital World : A Practical Guide - Mogaji, Emmanuel (SAGE Publications, Ltd. (UK), 2024)
Do you want to understand and apply qualitative research methods in a digital context? This book will help you navigate the complexities of digital access and fluency, ensuring a broad lens on research methodologies. From step-by-step guides to innovative frameworks, each chapter is crafted to give you the confidence to carry out cutting-edge qualitative research.  This book will provide you with: The knowledge you need to advance your qualitative research understanding across all disciplines. A practical reflection of the application of relevant research methodologies. An overview of research ideas, cases, and examples. With a wealth of exercises and examples, this book will become a reference point for qualitative research in the digital context by adopting a case-in-point approach for students across all social science disciplines.